Infectious Complications in Patients with Primary Glomerulonephritis over 10 Years: A Single-Center Experience in Turkey - Rezzan Eren Sadioglu; Sahin Eyupoglu; Siyar Erdogmus; Gizem Kumru Sahin; Fugen Yoruk; Sim Kutlay; Kenan Keven; Sehsuvar Erturk; Sule Sengul (Karger Publishers, 2020)
Introduction: Infections can play an important role in the mortality and morbidity of patients with glomerulonephritis. However, the frequency of infectious complications in primary glomerulonephritis and their burden to the healthcare managements are not clear. Methods: We evaluated the infectious complications in patients with biopsy-proven focal segmental glomerulosclerosis, membranous glomerulonephritis, IgA nephropathy, minimal change disease, membranoproliferative glomerulonephritis, and chronic glomerulonephritis during the last 10 years in a single center. We recorded the demographic, clinical, and laboratory characteristics; treatment modalities; infectious episodes; and infection-related mortality and morbidity of the patients. Results: Of the patients, 154 (63.6%) received immunosuppressive treatment and 88 (34.4%) were followed up under conservative treatment. Overall, 118 infectious episodes were noted in 64 patients, with an infection rate of 0.20 per patient-year. Total infectious complications were higher in the immunosuppressive group than in the conservative group (42.1 vs. 23.3%, p = 0.005). Infection-related hospitalizations were also higher in the immunosuppressive group (p = 0.01). The most frequently infected area was the lungs (15.7%). Although bacterial infections were the most common in both groups, 14.9% of the immunosuppressive group had cytomegalovirus (CMV) replication. Age >50 years (OR 2.19, p = 0.03), basal serum albumin <2.5 g/dL (OR 2.28, p = 0.02), cyclophosphamide (OR 2.43, p = 0.02), and cyclosporine (OR 2.30, p = 0.03) were independently associated with experiencing infectious episodes. Conclusions: Because of high seropositivity for CMV in Turkey, it might be a wise approach to use prophylactic antiviral drugs in patients treated with immunosuppressive treatments. Close monitoring of patients with primary glomerulonephritis, especially those treated with immunosuppressive therapy, is important for reducing infection-related morbidity and mortality.